The Working Class Family Economy: Montréal, 1861-1881 - Bradbury, Bettina (Concordia University, 1984)
The family economy of the working class in the period of early industrial capitalism is examined in this thesis. Changes in the involvement of family members in wage labour, in education, in non-wage and domestic labour at home as well as in patterns of marriage, childbearing and residential arrangements are assessed. Analysis is based on data collected from the manuscript censuses for two working class Montreal wards, Ste. Anne and St. Jacques between 1861 and 1881. This is complemented by information from other contemporary quantitative and descriptive sources. The roles of fathers, children and mothers are examined in separate chapters for age and gender combined with class position to determine people's roles in the family and in the wider economy. Within the working class, the level and regularity of men's wages set the contours of the family economy conditioning the need for and the nature of other survival strategies. Differences of around 25 cents a day translated over a year into the possibility of divergent standards of living, roughly dividing the working class into separate, identifiable fractions. Each favoured particular survival strategies and exhibited different patterns of family labour commitment, marriage, reproduction and residence. Over this period the contours of working class youth were reshaped. Growing numbers of children aged six to twelve attended school. An increasing proportion of older children were drawn into wage labour. Boys were more likely to work for wages than girls. Girls worked in a narrower range of jobs and for a shorter span of their lives. On marriage most ceased wage earning. With whatever money others earned, they tried to ensure that the family's wage labourers faced each day sufficiently fed, clothed and rested to work. And, in abysmal living conditions they produced and socialized the next generation of workers. Occasionally seeking wage labour themselves, raising animals or gardens, or sharing their homes helped some women to come closer to balancing family budgets. Working class women remained, however, both economically and legally dependent on their husbands. This dependence was highlighted in the problems that widows faced when they tried to raise and feed a fatherless family.
Keywords: Academic theses; Thèses et écrits académiques; dissertations